Retrospective Investigation of Duck Diseases and Their Temporal Distribution in Sylhet: Passive Surveillance (Research in Agriculture Livestock and Fisheries, 2025)
A cross-sectional retrospective study was performed from September 2020 to December 2024 at Field Disease Investigation Laboratory (FDIL), Sylhet, in Bangladesh to determine the prevalence of different duck diseases and to explore the temporal distribution of important duck diseases in Sylhet. Data were collected passively from the registers of FDIL, Sylhet, and a total of 472 pieces of duck information about either infected or dead ducks were collected. The prevalence of duck plague was significantly higher (45.3%; 95% CI: 40.78-49.95) among all duck diseases documented during the study period. Duck cholera was the second most prevailing disease (28%), followed by AI, salmonellosis, DVH, NE, Colibacillosis, Mycoplasmosis etc. The current study observed a relatively high percentage of DP in mature ducks (66.20%; 95% CI: 53.99-77.00%) compared to the younger birds and in the summer season compared to the rest of the season. On the other hand, the young-aged group of ducks had a comparatively high frequency (33.96%; 95% CI: 27.62- 40.76%) of duck cholera compared to mature birds, and no prevalence was observed for birds aged above 269 days. This study revealed the duck disease burden from a clinical aspect, which will be beneficial for the concerned authority to take preventive measures against the diseases. Additionally, further research on duck diseases with temporal distribution will be facilitated by the study findings.Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 85-92